Effects of acute ammonia exposure on oxidative stress, endoplasmic reticulum stress and apoptosis in the kuruma shrimp (Marsupenaeus japonicus) - Haixin Ou; Jiahao Liang; Jianyong Liu (Aquaculture Reports, 2022)
Ammonia is one of the main toxic substances in aquaculture water and causes serious physiological harm to aquatic animals. In the present study, we investigated the effects of ammonia exposure on antioxidant defense, endoplasmic reticulum stress and apoptosis in the Marsupenaeus japonicus hepatopancreas. Shrimp in three experimental groups (control, 15 mg/L and 45 mg/L ammonia) were sampled at 6, 12, 24, 48 and 96 h. The activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPX), and the corresponding relative mRNA expression levels in the hepatopancreas, showed slight or obvious increases during the early stage of ammonia exposure, and then significantly decreased after 48 h or 96 h of exposure, while the malondialdehyde (MDA) content increased continuously during ammonia exposure. In addition, the mRNA expression of nuclear factor erythroid 2-related factor 2 (Nrf2) showed a similar regulation pattern to the antioxidant enzymes, whereas Kelch-like ECH associated protein 1 (Keap1), a negative regulator of Nrf2, showed the opposite pattern. Moreover, the relative mRNA expression levels of heat shock proteins (HSP70 and HSP90), endoplasmic reticulum stress marker (GRP78) gene and key unfolded protein response (UPR)-related genes (eIF2α, ATF4, IRE1 and XBP1) increased significantly during the early stage of ammonia exposure. Taken together, these results indicate that the antioxidant system, Nrf2-Keap1 signaling pathway, UPR and heat shock proteins play protective roles in ammonia-induced oxidative stress and apoptosis in M. japonicus. However, ammonia exposure also induced up-regulation of apoptosis genes (Caspase 3 and ASK1) levels, indicating that cell apoptotic may relate to oxidative stress. After 96 h of exposure to 45 mg/L ammonia, down-regulation of HSP70 and HSP90 gene transcription levels suggests that the protein synthesis system may be destroyed under severe ammonia-induced oxidative stress. Our results provide new insights into the mechanism through which crustaceans resist ammonia stress.